1980
DOI: 10.1007/bf00016585
|View full text |Cite
|
Sign up to set email alerts
|

Strain-rate dependent fracture initiation

Abstract: A B S T R A C T The theory of linear elastic dynamic fracture mechanics for Heaviside loading of an isolated crack is employed to formulate the response to constant strain-rate loading of a single crack. Numerical integration of the Heaviside solution is shown to lead to fracture initiation stresses that are dependent upon the imposed strain rate. These fracture initiation stresses are also shown to be relatively independent of the crack size and crack shape. The results are used to explain the strain-rate dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(42 citation statements)
references
References 5 publications
4
38
0
Order By: Relevance
“…Crack propagation induces a local stress release. This aspect is in a good agreement with the fineness of the fragments reported in [53][54][55][56][57][58][59][60][61][62][63][64].…”
Section: Hard Metals: Overview and Some Propertiessupporting
confidence: 92%
“…Crack propagation induces a local stress release. This aspect is in a good agreement with the fineness of the fragments reported in [53][54][55][56][57][58][59][60][61][62][63][64].…”
Section: Hard Metals: Overview and Some Propertiessupporting
confidence: 92%
“…Hence, the anisotropic property of Barre granite due to the presence of preferred microcracks has less influence on dynamic catastrophic failure. In addition, based on their study, KIPP and GRADY (1980) found the insensitivity of the fracture stress over a large range of crack sizes, which suggests that the inherent flaws in the rock are the basis for the rate dependence of fracture stress, i.e., it is a geometric and not a material effect . Thus, the effects of anisotropy on the tensile strength of Barre granite appear to be overshadowed by the dynamic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Strain rate dependent spall has been investigated through the time-dependent stress intensity factor of a single crack [Kipp et al, 1980], through statistical crack distributions , and, more recently, through thermodynamic energy conditions for spall fracture . These studies all suggest the same functional dependence for the spall strength, and the latter provides the strain rate dependent criteria.…”
Section: Tt^cmentioning
confidence: 99%